Engineering Degree Courses-Focus on Outcome - Chugh, C. K.; Dixit, R. K. (Journal of Engineering Education Transformations, 2011)
Various kinds of industries use engineering to generate and maintain economy in the country by creating goods and services. The responsibility of academia is to provide quality-engineering education, so that the graduates are able to perform as per the requirement of industries. It is assumed by academic world that engineering education system is developing the required abilities in degree pass outs, while the industries have always complaining about the quality of fresh graduates. In USA, researches are being conducted by academia to find out the extent of satisfaction on the abilities being developed in fresh graduates. The regular feedbacks are being sought from the world of employment on extent of development and further requirement of abilities. In our country, these kinds of researches need to be conducted continuously to improve the quality of education.